Analisis Komparatif Buku Panduan Terjemah Arab-Indonesia - Prasetiadi, Yan Septiana; Raihan, Ulfah (Universitas Al Azhar Indonesia, 2025)
Translation guidebooks play a crucial role in both academic and practical contexts. Among the notable examples are Mafaza: Pintar Menerjemahkan Bahasa Arab-Indonesia and Buku Pintar Menerjemah Arab-Indonesia. This study aims to describe the structure and content of these two books, as well as analyze their respective strengths and weaknesses. Employing a content analysis method with a qualitative approach, the research reveals that both books address the theory and practice of translation while avoiding overly literal translation techniques. Mafaza stands out for its wealth of practical translation formulas, making it particularly suitable for beginner translators. In contrast, Buku Pintar Menerjemah Arab-Indonesia excels in its comprehensive theoretical explanations, making it more appropriate for readers seeking a deeper understanding of translation theory. Consequently, Mafaza is less ideal for those pursuing in depth theoretical knowledge, and Buku Pintar not be suitable for novice learners.Keywords – Translation Handbook, Translation Practice, Translation Theory.